2020
DOI: 10.1101/2020.10.23.20218511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale population analysis of SARS-CoV-2 whole genome sequences reveals host-mediated viral evolution with emergence of mutations in the viral Spike protein associated with elevated mortality rates

Abstract: Background We aimed to further characterize and analyze in depth intra-host variation and founder variants of SARS-CoV-2 worldwide up until August 2020, by examining in excess of 94,000 SARS-CoV-2 viral sequences in order to understand SARS-CoV-2 variant evolution, how these variants arose and identify any increased mortality associated with these variants. Methods and Findings We combined worldwide sequencing data from GISAID and Sequence Read Archive (SRA) repositories and discovered SARS-CoV-2 hypermuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 89 publications
4
23
0
Order By: Relevance
“…The Spike: S477N mutation has been shown to enhance folding and binding to the angiotensin-converting enzyme 2 (ACE2) receptor. 25,26 Consistent with our results, Spike: S477N has been correlated with higher CFR. 25 Spike: V1176F mutation has been predicted to increase stability of the protein and flexibility of the trimeric stalk.…”
Section: Time Place Mutationsupporting
confidence: 90%
See 4 more Smart Citations
“…The Spike: S477N mutation has been shown to enhance folding and binding to the angiotensin-converting enzyme 2 (ACE2) receptor. 25,26 Consistent with our results, Spike: S477N has been correlated with higher CFR. 25 Spike: V1176F mutation has been predicted to increase stability of the protein and flexibility of the trimeric stalk.…”
Section: Time Place Mutationsupporting
confidence: 90%
“…25,26 Consistent with our results, Spike: S477N has been correlated with higher CFR. 25 Spike: V1176F mutation has been predicted to increase stability of the protein and flexibility of the trimeric stalk. 25 It is also reported that the Spike: V1176F, ORF6: I33T, and ORF1a: L3930F mutations are correlated with increased CFR in Brazil.…”
Section: Time Place Mutationsupporting
confidence: 90%
See 3 more Smart Citations